Coronary CTA Would Facilitate Invasive Angiography in Patients With Acute Coronary Syndrome and Coronary Bypass Grafting History - Ma, Shaowei; Zhou, Ke; Ma, Yue; Ma, Quanmei; Hou, Yang (Frontiers in Cardiovascular Medicine, 2022)
Background The uncertainties of grafts’ ostium and patency would cause prolonged procedure/fluoroscopy time and extra contrast agent consumption of the invasive coronary angiography (ICA) in patients with coronary artery bypass grafting (CABG) history. This study was conducted to evaluate whether the identification of grafts’ ostium and patency by coronary computed tomographic angiography (CTA) could facilitate ICA procedure. Methods Patients with acute coronary syndrome (ACS) and CABG history who underwent ICA during hospitalization were enrolled. The patients were divided into CTA-ICA group and direct ICA group according to whether a coronary CTA was performed before ICA. The complete direct ICA was defined by successful selective angiography of all grafts. The procedure/fluoroscopy time and contrast agent consumption of ICA were compared. Results There were 14 patients in CTA-ICA group and 24 patients in direct ICA group. In direct ICA group, twelve cases were conducted complete ICA. The CTA-ICA group had reduced procedure time (17.8±7.1 Vs. 25.9±15.4 mins, p<0.01), fluoroscopy time (4.6±2.3 Vs. 9.8±5.3 mins, p<0.01), and less contrast agent consumption (30.4±5.6 Vs. 49.8±20.9 ml, p<0.01) than direct ICA group. In subgroup analysis, the incomplete direct ICA had the longest procedure (32.8±16.5 mins) or fluoroscopy (12.0±5.5 mins) time and the most contrast agent consumption (58.3±25.8 ml), while the difference between CTA-ICA and complete direct ICA groups was non-significant. Conclusion The CTA would facilitate invasive angiography in CABG patients by reducing procedure/fluoroscopy time and contrast agent consumption.